State-Of-The- Art Sensors Technology in France 2016 - Nicole Jaffrezic-Renault (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
This Special Issue aims to provide a comprehensive overview of state-of-the-art sensors technology in France. It includes research articles that consolidate our understanding of the state-of-the-art in this area and also four reviews on hot fields in sensor technology (nanomaterials, electronic tongue and optical fibre networks).